Gender stereotypes across the ages: On-line processing in school-age children, young and older adults - Siyanova-Chanturia, Anna; Warren, Paul; Pesciarelli, Francesca; Cacciari, Cristina (Frontiers in Psychology, 2015)
Most research to date on implicit gender stereotyping has been conducted with one age group – young adults. The mechanisms that underlie the on-line processing of stereotypical information in other age groups have received very little attention. This is the first study to investigate real time processing of gender stereotypes at different age levels. We investigated the activation of gender stereotypes in Italian in four groups of participants: third- and fifth-graders, young and older adults. Participants heard a noun that was stereotypically associated with masculine (preside “headmaster”) or feminine (badante “social care worker”) roles, followed by a male (padre “father”) or female kinship term (madre “mother”). The task was to decide if the two words – the role noun and the kinship term – could describe the same person. Across all age groups, participants were significantly faster to respond, and significantly more likely to press ‘yes’, when the gender of the target was congruent with the stereotypical gender use of the preceding prime. These findings suggest that information about the stereotypical gender associated with a role noun is incorporated into the mental representation of this word and is activated as soon as the word is heard. In addition, our results show differences between male and female participants of the various age groups, and between male- and female-oriented stereotypes, pointing to important gender asymmetries.